Comprehensive evaluation of the financial performance for intermediary institutions based on multi-criteria decision making method - Güler Aras; Nuray Tezcan; Özlem Kutlu Furtuna (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - The purpose of this paper is to assess the financial performance of the intermediary institutions that have operated in the Turkish capital markets taking the issue of bank-origin and non-bank-origin institutions into account. Design/methodology/approach - Financial performance of the intermediary institutions has been measured by the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method between the years 2005 and 2016. In order to implement the TOPSIS method, the relative importance of financial performance indicators has been determined by Entropy, survey results and considering equal weights approaches. Findings - Empirical findings indicate that the average performances of continuously operating intermediary institutions during the concerned period are above the average performance levels of all intermediaries. Additionally, the average rank of bank-origin intermediary institutions have been found higher than the non-bank origins for all years. This reveals that the average financial performance of the bank-origin intermediary institutions is higher than the average score of non-bank origins during the related years. Originality/value - This study is unique in terms of evaluating the performance of intermediary institutions in Turkish capital markets with a comprehensive framework. Determining the relative importance of financial performance indicators according to entropy, survey results and equal-weight approaches and revealing the average financial performance ranking methodology for bank-origin and non-bank-origin intermediary institutions have added value.
Keywords: 330; Survey; Financial performance; TOPSIS; Entropy; Capital markets; Intermediary institutions